Pattern recognition frequency-based feature selection with multi-objective discrete evolution strategy for high-dimensional medical datasets - Nematzadeh, Hossein; García-Nieto, José Manuel; Aldana-Montes, José Francisco; Navas-Delgado, Ismael (Elsevier, 2024)
Feature selection has a prominent role in high-dimensional datasets to increase classification accuracy, decrease the learning algorithm computational time, and present the most informative features to decision-makers. This paper proposes a two-stage hybrid feature selection for high-dimensional medical datasets: Maximum Pattern Recognition - Multi-objective Discrete Evolution Strategy (MPR-MDES). MPR is a rapid filter ranker that significantly outperforms existing frequency-based rankers in recognizing non-linear patterns, effectively eliminating a majority of non-informative features. Then, the wrapper Multi-objective Discrete Evolution Strategy (MDES) uses the remaining features and obtains sets of solutions which are automatically presented to decision-makers. The experiments conducted on large medical datasets demonstrate that MPR-MDES achieves considerable improvements compared to state-of-the-art methods, in terms of both classification accuracy and dimensionality reduction. In this sense, the proposal successfully performs when presenting informative feature sets to decision-makers. The implementation is available on https://github.com/KhaosResearch/MPR-MDES.
Keywords: Reconocimiento de formas (Informática); Sistemas informáticos; Feature selection; High-dimensional datasets; Filter; Wrapper; Multi-objective optimization